Laparoscopic cloasure of Duodenal ulcer perforation - Pangeni, Anang; Shakya, Vikal Chandra (Journal of Society of Surgeons of Nepal, 2016)
Introduction and Objective: Duodenal ulcer perforation creates a peritonitis which is sometimes hard to manage, especially with minimally invasive approach. This study is about laparoscopic approach to peritonitis due to duodenal ulcer perforation.Materials and Methods: It was a prospective study in patients presenting with duodenal perforation peritonitis to emergency of Civil Service Hospital from January 2013 to November 2015.Result: There were 6 patients (4 males and 2 females). The mean duration of presentation was 16+2.32 hrs. The mean operative time was 55+17.34 minutes. One patient developed right lower zone pneumonia which resolved on conservative management. There was no conversion.Conclusion: Laparoscopic management of duodenal perforation is a feasible procedure in select young patients who present early and without any without comorbities